1970
DOI: 10.1037/h0030017
|View full text |Cite
|
Sign up to set email alerts
|

Light- and dark-contingent bar pressing in the rat as a function of age and motivation.

Abstract: The effects of age and food deprivation on operant responding for light onset or light offset were determined for rats after operant-level pretests. Results were: (a) light onset had a reward value which was similar to that for light offset, (b) stimulus change was an equally effective reward for food-deprived or nondeprived rats, (c) the effects were invariant over the entire age range for mature rats, and (d) response rates were greater for food-deprived than nondeprived rats during all operant-level and sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It is also possible that control 5s pressed the bar to turn off the light. It has been shown that rats will learn to press a bar to decrease illumination in the chamber (e.g., Goodrick, 1970;Lockard, 1966). The purpose of the light was to increase the amount of frustration in Groups 15-0 and 15-1, since a previous study (Daly, 1969b) had shown that groups given frustration conditioning to apparatus cues plus a light jumped a hurdle faster to escape these cues than if frustration was conditioned only to the apparatus cues.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that control 5s pressed the bar to turn off the light. It has been shown that rats will learn to press a bar to decrease illumination in the chamber (e.g., Goodrick, 1970;Lockard, 1966). The purpose of the light was to increase the amount of frustration in Groups 15-0 and 15-1, since a previous study (Daly, 1969b) had shown that groups given frustration conditioning to apparatus cues plus a light jumped a hurdle faster to escape these cues than if frustration was conditioned only to the apparatus cues.…”
Section: Discussionmentioning
confidence: 99%
“…[22, 23, 24, 25]). However, lights have also been used as effective reinforcers during operant conditioning [2, 27, 14]. Experiment 1 aimed to determine whether a brief bright light serves as a punisher.…”
Section: Experiments 1: Punishmentmentioning
confidence: 99%
“…Further examination led Campbell and Messing [6] to suggest that light is likely aversive even at the lowest levels of illumination in rats. However, a considerable number of studies have proposed that light—at some levels—may not be aversive [36], and might even act as a reinforcer [2, 14, 40]. …”
mentioning
confidence: 99%
“…Numerous research findings have suggested that not only the switching on of light but also its switching off in the Skinner box serves as a reinforcement (Berlyne, Koenig & Hirota, 1966;Goodrick, 1970;Matysiak, 1980). Hence, theoretically at least, both variants of sensory reinforcement can be used as equivalent methods in stimulus seeking studies.…”
Section: Discussionmentioning
confidence: 99%